Что такое джунгли: [стихи / П. Глушко ; художник И. Шиповская] - Глушко П. (Мультфильмы-малышам, 2007)
Экземпляры: ф.4 (20151203) / Инвентарный номер: 47441 / Цена: 12.00 / Сис.шифр: Д / Авт.знак: Г 55 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6